2005
DOI: 10.1359/jbmr.041016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Action of Transient and Continuous PTH on Primary Osteoblast Cultures Expressing Differentiation Stage-Specific GFP

Abstract: Primary calvarial osteoblast cultures derived from type I collagen promoter-GFP reporter transgenic mice were used to examine progression of the osteoblast lineage. This system was validated by assessing the effect of PTH on osteoblast growth in real time. The anabolic effect of PTH seemed to be the result of enhanced osteoblast differentiation rather than expansion of a progenitor population.Introduction: Activation of green fluorescent protein (GFP) marker genes driven by Col1a1 promoter fragments has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 46 publications
5
46
0
Order By: Relevance
“…It has been shown that vascular smooth muscle cells and skeletal osteoblasts respond oppositely to the same stimuli, such as oxidized phospholipids and continuous activation of the PKA pathway (as in hyperparathyroidism) (3,24,(33)(34)(35)(36)(37), i.e. these factors promote osteoblastic differentiation of vascular cells but inhibit osteoblastic differentiation of bone cells.…”
Section: Table 2 Effect Of Pki On Tnf-␣ Induction Of Ranklmentioning
confidence: 99%
“…It has been shown that vascular smooth muscle cells and skeletal osteoblasts respond oppositely to the same stimuli, such as oxidized phospholipids and continuous activation of the PKA pathway (as in hyperparathyroidism) (3,24,(33)(34)(35)(36)(37), i.e. these factors promote osteoblastic differentiation of vascular cells but inhibit osteoblastic differentiation of bone cells.…”
Section: Table 2 Effect Of Pki On Tnf-␣ Induction Of Ranklmentioning
confidence: 99%
“…The Col2.3 promoter has been well characterized and specifically targets gene expression to mature osteoblasts (7)(8)(9)(10). Green fluorescent protein (GFP) transgenic mice using the same fragment of the type I collagen promoter to drive GFP expression (2.3Col-GFP) demonstrated that only cells with features of mature osteoblasts show fluorescence in vivo and in vitro (7,9). Microarray analysis data on this population of GFP-positive cells show it to be highly enriched for expression of mature osteoblast-specific genes such as osteocalcin, bone sialoprotein (BSP), and dentin matrix protein-1 (8).…”
mentioning
confidence: 99%
“…Previously, we have shown that primary calvarial osteoblast cultures derived from mice transgenic for promoter-driven stage-specific green fluorescent protein (GFP) marker genes pOBCol3.6GFP and pOBCol2.3GFP (24) respond to an early transient PTH exposure (from day 1 to 7) and, consequently, after the removal of PTH, acquire intensified expression of fluorescent markers and increased formation of mineralized bone nodules by day 21 (43). However, at day 21, the final DNA content in PTH-treated cultures was never higher than that of control cultures, making it unlikely that the early transient PTH exposure stimulates progenitor cell proliferation.…”
mentioning
confidence: 99%